Considerations on gestational and newborn anemia in Peru: a narrative review - Gonzales, Gustavo F. (2023)
Anemia during pregnancy is considered a public health problem, due to the alarmingprevalence worldwide. The measure chosen by various governments is massive ironsupplements. However, there is currently contradictory evidence on iron intake,excess consumption, and potential risks during pregnancy for both the motherand child. For gestation, an additional 1 gram of iron is required for the mother,fetus, placenta, and delivery. This generates an increase in red mass of 20% but toavoid hemoconcentration the plasma volume expands by almost 50% generating aphysiological hemodilution. For pregnant women, no criteria have been establishedto differentiate iron deficiency anemia and physiological anemia due to the normalprocess of hemodilution. In the case of Peru and countries with high altitude residentpopulation, there is an additional problem, the hemoglobin correction factor forhigh altitude residence, which is a mathematically and arbitrarily determined value.Recent evidence suggests that this factor should be reevaluated because it does notconsider ethnicity and generational time of residence at high altitude. The presentreview provides an update and discussion of the diagnostic criteria for anemia, ironsupplementation, the hemoglobin correction factor for altitude of residence, and theimpact of environmental pollution on the gestation process.